Liquid Metal Biomaterials Principles and Applications - Liu, Jing (Springer Series in Biomaterials Science and Engineering,, 2018)
This is the first-ever book to illustrate the principles and applications of liquid metal biomaterials. Room-temperature liquid metal materials are rapidly emerging as next-generation functional materials that display many unconventional properties superior to those of conventional biomaterials. Their outstanding, unique versatility ("one material, diverse capabilities") opens many exciting opportunities for the medical sciences. The book reviews representative applications of liquid metal biomaterials from both therapeutic and diagnostic aspects. It also discusses related efforts to employ liquid metals to overcome today's biomedical challenges. It will provide readers with a comprehensive understanding of the technical advances and fundamental discoveries on the frontier, and thus equip them to investigate and utilize liquid metal biomaterials to tackle various critical problems.